Junie B., first grader : jingle bells, Batman smells! (P.S. so does May) - Park, Barbara; Brunkus, Denise (New York : Random House, 2005)
Junie B. Jones wishes that May would stop being such a tattletale, but when she is stuck as May's Secret Santa it becomes real trouble.
"A Stepping Stone book."
Keywords: Talebearing; Gifts; Schools